Immunisation of cattle against East Coast fever. Experience in Zanzibar - Biwi, K.M.; Rabia, R.; Dolan, T.T. (International Livestock Centre for Africa, 1993)
Concern about the introduction of the T. parva strain unknown in Zanzibar by using the Muguga cocktail for immunisation against East Coast fever led the government to request ILRAD to develop a vaccine stabilate using T. parva strains found in Unguja and Pemba. Tests by researchers finally come up with the Zanzibar south stabilate and the Pemba Mnarani stabilate for immunisation against ECF in Unguja and Pemba, respectively. Trials carried out in Unguja showed that the Zanzibar south stabilate protected cattle against ECF after immunisation. Field immunisation, which started in 1990, has been well accepted by smallholder farmers. Five hundred Bos taurus cattle and their crosses have been immunised and the work is still in progress. However, further work on immunisation against other tick-borne diseases, particularly babesiosis, needs to be undertaken. Trials in Pemba which have lagged behind need to be completed so that field immunization in Pemba can start as soon as possible. Experience gained so far indicates that immunisation against ECF coupled with strategic dipping is crucial for the development of smallholder dairy industry in Zanzibar.